Middle–Upper Ordovician radiolarians in Hunan and Jiangxi Provinces, South China: Implications for the sedimentary environment and nature of the Nanhua basin. (1st August 2019) - Zheng, Ning; Li, Tingdong; Cheng, Muwei
Graphical abstract: Highlights: O2 2 -O3 1 chert and radiolarians indicate a placid sedimentary environment. O1-2 radiolaria indicates that the Nanhua basin was connected to ocean. Abundances of O2 2 -O3 1 radiolarian in Hengyang–Ji'an show the basin center. O2 2 -O3 1 rocks in South China should be developed in an environment of continental slope–basin. Abstract: The Yanxi and Duiershi formations of the Middle-Upper Ordovician in South China are composed of black, grayish black, and dark gray thin-bedded cherts and siliceous slates, rich in carbonaceous materials and pyrite. Horizontal beddings are developed. The strata contain randomly distributed fossils. Radiolarians are discovered in the Loudi, Yongzhou, Hengyang, Ji'an and Ganzhou sections. The Radiolaria from two sections are identified as Protoentactinia sp. Abundances of radiolarian in the central area of Hunan and Jiangxi Provinces are higher than in the southern area. The strata become thickened while the amounts of siliceous materials are decreased and argillaceous contents are increased from northwest to southwest for the Yanxi and Duiershi formations. The lithology gradually changes from carbonate rocks in the north to clastic rocks in the south. δ 30 Si values of chert and siliceous slate range from −0.6 to 1.18 with Al2 O3 /(Al2 O3  + Fe2 O3 ), MnO/TiO2, LaN /CeN, Ce/Ce *, and (La/Yb)N ratios of 0.65–0.97, 0.01–0.16, 0.99–1.27, 0.85–1.10, and 0.91–1.66, respectively. The SiO2 and TiO2 average contents are 89.08% and 0.27%. The SiO2 contents decrease while the TiO2 increase from northwest to southeast. They have similar the REE concentration with no obvious Eu anomalies. The Yanxi and Duiershi formations were deposited predominately in a bathyal environment on the continental slope–basin and the seawater was stagnant. In the Middle–early Late Ordovician, the Nanhua basin occupied a rather large area and sedimentary rocks in the region around Hengyang–Ji'an were deposited in the basin center with terrigenous source derived from the southeast.